Eksplorasi Media Sosial: Mengungkap Mata Pisau Jalan Pintas Menuju Keadilan dalam Birometri Hukum - Allowisius Bawi; Liboria G. Atek; Mauritius Kelanit; Lestari Wulandari S (UNES Law Review, 2023)
In the ever-evolving digital era, the presence of social media has significantly impacted legal systems and the enforcement of justice. This article delves into a thorough exploration of the role of social media as a shortcut tool that can reveal gaps in the bureaucracy of law enforcement. The focus is on the concept of the "Knife's Edge," reflecting the positive and negative potential of social media in either supporting or hindering the pursuit of justice. Through a sharp analysis of the bureaucratic aspects, this article discusses how social media can serve as an effective means to strengthen or undermine the foundations of law enforcement. Thus, this research provides a profound understanding of the dynamics of interaction between social media and legal bureaucracy, initiating a discussion on its critical role in achieving justice goals in modern society.